Development of Problem Based Learning Method To Increase Students’ Mathematical Problem Solving Ability at Numbers Theory Courses - Asep Sahrudin (International Journal of Trends in Mathematics Education Research, 2019)
This article presents development reasearh result of problem based learning method to increse students’mathematical problem solving ability conducted at 4th semester students in 2016 academic years at numbers theory course. The aim of the research is to describe development process of problem based learning method corresponding theoretical concepts to increase mathematical problem solving ability with learning device includes: (a) RPS and (b) learning media which be able to be applied in mathematical learning process and testing learning method which has been developed.This research uses mixed method, qualitative method reviews and describes implementation process of learning method, while quantitative method uses experimental design (pretest and postest) to discover its effects towards students whether learning method which developed proven effective to increase students’ problem solving ablity. Based on the results of research and discussion, the study concluded that the strategy of mathematics which has been developed and tested can improve the ability of solving mathematical problems very well (excellent).